Integrative mouse and human mRNA studies using WGCNA nominates novel candidate genes involved in the pathogenesis of major depressive disorder. (December 2013) - Malki, Karim; Tosto, Maria Grazia; Jumabhoy, Irfan; Lourdusamy, Anbarasu; Sluyter, Frans; Craig, Ian; Uher, Rudolf; McGuffin, Peter; Schalkwyk, Leonard C
Aim: This study aims to identify novel genes associated with major depressive disorder and pharmacological treatment response using animal and human mRNA studies.Materials & methods: Weighted gene coexpression network analysis was used to uncover genes associated with stress factors in mice and to inform mRNA probe set selection in a post-mortem study of depression.Results: A total of 171 genes were found to be differentially regulated in response to both early and late stress protocols in a mouse study. Ten human genes, orthologous to mouse genes differentially expressed by stress, were also found to be dysregulated in depressed cases in a human post-mortem brain study from the Stanley Foundation Brain Collection.Conclusion: Several novel genes associated with depression were uncovered, including NOVA1 and USP9X . Moreover, we found further evidence in support of hippocampal neurogenesis and peripheral inflammation in major depressive disorder. Original submitted 3 July 2013; Revision submitted 5 August 2013